Evaluating the risk of osteoporosis-related adverse events with proton pump inhibitors: a pharmacovigilance study - Di, Jingkai; Yang, Nan; Zhao, Yicong; Chen, Shuai; Guo, Zijian; He, Dongdong; Xiang, Chuan (Frontiers in Pharmacology, 2025)
BackgroundProton pump inhibitors (PPIs) are the most effective antacids and are widely used in the treatment of acid-related diseases. However, the impact of PPIs on bone remains controversial. This study aimed to explore the association between PPIs and osteoporosis-related adverse events in the real world.Materials and methodsData from the United States Food and Drug Administration Adverse Event Reporting System from the first quarter of 2004 to the third quarter of 2024 were included in this study. Four pharmacovigilance analyses, reporting odds ratio (ROR), proportional reporting ratio (PRR), information component (IC), and Empirical Bayes geometric mean (EBGM) were used to explore the association between PPIs use and osteoporosis-related adverse events. In addition, we used the Bonferroni corrected P values and 95% confidence interval (95%CI). Meanwhile, the situation of different age and gender groups was examined using subgroup analysis. Additionally, evoked times and Weibull distributions were used to analyze the data further.ResultsAt the Primary terms level, esomeprazole, omeprazole and pantoprazole were found to have positive adverse event signals. However, at the overall dimension level of Standardized Medical Dictionary for Regulatory Activities (MedDRA) query, only esomeprazole (ROR: 8.83, 95%CI: 8.53–9.13, P < 0.001) and omeprazole (ROR: 1.54, 95%CI: 1.44–1.66, P < 0.001) signals were positive. Based on subgroup stratification, the study showed that the signal intensity of adverse events was stronger among women and older adults. Weibull distribution analysis indicated that the incidence of osteoporosis-related adverse events of esomeprazole increased gradually over time, while the risk of omeprazole did not show regular spatial and temporal distribution.ConclusionThis study comprehensively reports the risk of osteoporosis in the clinical use of five commonly used PPIs, which provides certain ideas and insights for the clinical prevention of such adverse events.